"Bliis-Survey" And "Fsmu" Technology In A Practical Training On The Subject "Chemistry Of Coordination Compounds" (Eurasian Research Bulletin, 2024)
This article provides examples of the application of "Blitz-survey" and "FSMU" technologies in a practical exercise on the topic "Chemistry of coordination compounds". First of all, information on the Blitz-survey method and FSMU technologies, transfer technology, stages of implementation of this technology are studied and methods of application in practice are described.